Comparative pharmacokinetic study of six lignans in normal and diabetic rats after oral administration of Saururus chinensis extract by LC–MS/MS. (28th October 2021) - Chen, Hongjiang; Luo, Yiyuan; Liu, Jianan; Chen, Jianwei; Chen, Yong; Li, Xiang
Abstract: Saururus chinensis (SC) possesses significant anti‐diabetic activity and lignans were its major bioactive compounds. In this study, a rapid and sensitive ultra‐high‐performance liquid chromatography–tandem mass spectrometry (UHPLC–MS/MS) method was established for simultaneous quantification of six lignans, namely (‐)‐(7 R, 8 R )‐machilin D (1 ), verrucesin (2 ), rel ‐(7 S, 8 S, 7′ R, 8′ R )‐3, 3′, 4, 4′, 5, 5′‐hexamethoxy‐7.O.7′, 8.8′‐lignan (3 ), manassantin A (4 ), manassantin B (5 ), and saucerneol F (6 ) in rat's plasma. It was validated with acceptable linearity ( r  ≥ 0.9922), accuracy (80.42–95.17%), precision (RSD ≤ 12.08%), and extraction recovery (80.36–93.45%). The method was successfully applied to the comparative pharmacokinetic study of the six lignans in normal and diabetic rats after oral administration of SC extract. Results showed that the areas under the plasma concentration‐time curve (AUC0 → t and AUC0 → ∞ ) of (‐)‐(7 R, 8 R )‐machilin D, rel ‐(7 S, 8 S, 7′ R, 8′ R )‐3, 3′, 4, 4′, 5, 5′‐hexamethoxy‐7.O.7′, 8.8′‐lignan, manassantin B, and saucerneol F in diabetic rats were significantly increased, and the plasma clearance (CL) of (‐)‐(7 R, 8 R )‐machilin D in diabetic rats was significantly decreased. However, the AUC0 → t and AUC0 → ∞ of verrucesin were significantly decreased, and its CL was significantly increased in diabetic rats compared with those in normal rats. These results indicated that there were remarkable differences in the pharmacokinetic parameters between the normal and diabetic rats. The pharmacokinetic studies might be beneficial for the clinical use of SC as hypoglycemic agent.